Hyperoxia‐induced miR‐342‐5p down‐regulation exacerbates neonatal bronchopulmonary dysplasia via the Raf1 regulator Spred3. (9th April 2021) - Wen, Xin; Zhang, Hui; Xiang, Bo; Zhang, Weiyu; Gong, Fang; Li, Shiling; Chen, Hongyan; Luo, Xuan; Deng, Juan; You, Yaoyao; Hu, Zhangxue; Jiang, Changke
Abstract : Background and Purpose: Bronchopulmonary dysplasia (BPD) is the most prevalent chronic paediatric lung disease and is linked to the development of chronic obstructive pulmonary disease. MicroRNA‐based regulation of type II alveolar epithelial cell (T2AEC) proliferation and apoptosis is an important factor in the pathogenesis of BPD and warrants further investigation. Experimental Approach: Two murine models of hyperoxic lung injury (with or without miR‐342‐5p or Sprouty‐related, EVH1 domain‐containing protein 3 [Spred3] modulation) were employed: a hyperoxia‐induced acute lung injury model (100% O2 on postnatal days 1–7) and the BPD model (100% O2 on postnatal days 1–4, followed by room air for 10 days). Tracheal aspirate pellets from healthy control and moderate/severe BPD neonates were randomly selected for clinical miR‐342‐5p analysis. Key Results: Hyperoxia decreased miR‐342‐5p levels in primary T2AECs, MLE12 cells and neonatal mouse lungs. Transgenic miR‐342 overexpression in neonatal mice ameliorated survival rates and improved the BPD phenotype and BPD‐associated pulmonary arterial hypertension (PAH). T2AEC‐specific miR‐342 transgenic overexpression, as well as miR‐342‐5p mimic therapy, also ameliorated the BPD phenotype and associated PAH. miR‐342‐5p targets the 3′UTR of the Raf1 regulator Spred3, inhibiting Spred3 expression. Treatment with recombinant Spred3 exacerbated the BPD phenotype and associated PAH. Notably, miR‐342‐5p inhibition under room air conditions did not mimic the BPD phenotype. Moderate/severe BPD tracheal aspirate pellets exhibited decreased miR‐342‐5p levels relative to healthy control pellets. Conclusion and Implications: These findings suggest that miR‐342‐5p mimic therapy may show promise in the treatment or prevention of BPD. Abstract : miR‐342‐overexpressing bronchopulmonary dysplasia (BPD) mice were shown to have ameliorated lung morphometry, reduced apoptosis levels and increased pulmonary vessel density when compared to wild‐type BPD mice on postnatal day 14 (PND14).